2020
DOI: 10.1016/j.cptl.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The use of social media as a tool to educate United Kingdom undergraduate pharmacy students about public health

Abstract: Background and purpose: The role of community pharmacists (CPs) in England now includes public health service delivery, which is deemed to be an essential pharmacy service. Pharmacy students need "real-life" experience to develop the skills required. A blended learning approach incorporating offline and online elements may be effective. In particular, using social media (SM) as a teaching tool could have dual benefits-students are engaged in a medium that they enjoy using and they learn how to use SM in a prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our opinion, this is due to the specific features of the communication process itself. We consider it appropriate to supplement blended learning with various communication forms in a foreign language through online services and social media (Crilly & Kayyali, 2019; Lo pez-Carril et al, 2020; Manca, 2020). We use Google Hangouts primarily, as it is already integrated with the Google Classroom platform.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this is due to the specific features of the communication process itself. We consider it appropriate to supplement blended learning with various communication forms in a foreign language through online services and social media (Crilly & Kayyali, 2019; Lo pez-Carril et al, 2020; Manca, 2020). We use Google Hangouts primarily, as it is already integrated with the Google Classroom platform.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) is an evolving tool that has been utilized in medicine and healthcare in the past years [30]. AI uses several methods like computer vision, natural language processing, and machine learning for pattern recognition, prediction, and data analysis.…”
Section: Social Media Crowdsourcing and Artificial Intelligence In Pu...mentioning
confidence: 99%
“…AI uses several methods like computer vision, natural language processing, and machine learning for pattern recognition, prediction, and data analysis. For these reasons, researchers have suggested that AI has the potential to improve public health [30]. A study conducted in the United Kingdom in 2021 explored how AI enables social media analysis on Facebook and Twitter for use in contact-tracing apps [31].…”
Section: Social Media Crowdsourcing and Artificial Intelligence In Pu...mentioning
confidence: 99%
“…Artificial intelligence (AI) is an evolving tool that has been utilized in medicine and healthcare in the past years [31]. AI uses several methods like computer vision, natural language processing, and machine learning for pattern recognition, prediction, and data analysis.…”
Section: Social Media Crowdsourcing and Artificial Intelligence In Pu...mentioning
confidence: 99%
“…AI uses several methods like computer vision, natural language processing, and machine learning for pattern recognition, prediction, and data analysis. For these reasons, researchers have suggested that AI has the potential to improve public health [31]. A study conducted in the United Kingdom in 2021 explored how AI enables social media analysis on Facebook and Twitter for contact-tracing apps use [32].…”
Section: Social Media Crowdsourcing and Artificial Intelligence In Pu...mentioning
confidence: 99%